Darío and the conflicts in Central America in 1890 - Troncoso Castillo, Christian David (2019)
This research studies Ruben Darío’s stories “El dios bueno” and “Betún y sangre”, the first stories of a serie of six, called “New stories”, a compilation that the writer wanted to publish, but he never do. The name of the hypothetic book is relevant to research because says that the writer had reasons to disattend what he made in Azul… We propose, in case of the “El dios bueno” and “Betún y sangre” stories, appears the politic and social element as motiv and mobilizer of the actions, thus, is significant studying of the power relations.The advent of politic theme have an explication on the own publication context of the stories, because they were written while Dario work like war chronicler; Darío uses the style of that discursive genres like verisimilitude procedures in the middle of descriptions, they clearly show real places.